Radiocarbon Chronology of Black-Sea Sediments - Jones, G. A.; Gagnon, A. R. (Deep-Sea Research Part I-Oceanographic Research Papers, 1994)
Accelerator Mass Spectrometer (AMS) radiocarbon analyses have been made on 102 samples from 12 sediment cores and 23 samples from two water column profiles. These materials, collected during the first leg of the 1988 joint U.S.-Turkish Black Sea Expedition, provide the most comprehensive radiocarbon chronology of Black Sea sediments vet attempted. Radiocarbon analyses from carefully collected box cores and a molluse shell collected live in 1931 suggest the prebomb surface waters had a DELTAC-14 value of -55 parts per thousand (460 years) and that the maximum detrital correction for radiocarbon ages of Unit I sediments is 580 years for the organic carbon and 260 years for the carbonate fractions. Evidence does not support the 1430-2000 year pre-bomb surface water and/or detrital corrections argued for in past studies. The best estimates for the age of the beginning of the final invasion of the coccolithophore Emiliania huxleyi (Unit 1/2 boundary of Ross and DEGENS, 1974, The Black Sea-geology, chemistry and biology, pp. 183-199) and the age of the first invasion of E. huxleyi (Unit I/II boundary of HAY et al., 1991, Deep-Sea Research, 38, S1211-S1235) are 1635 +/- 60 and 2720 +/- 160 years BP, respectively. Sapropel formation began at approximately 7540 +/- 130 years BP at all depths in the basin, a pattern in disagreement with those predicted by existing time-evolution models of sapropel formation for this basin. Our data suggest that the oxic-anoxic interface has remained relatively stable throughout the Holocene, is controlled largely by the physical oceanography of the basin, and has not evolved as assumed by previous workers.
Nm252Times Cited:121Cited References Count:44